2007
DOI: 10.1080/08880010701451467
|View full text |Cite
|
Sign up to set email alerts
|

GOTPUREBLOOD IN FETAL RATS?

Abstract: Have you felt frustration when fetal blood is needed for your studies in rats, or have you been concerned about fetal rat "blood" collected from decapitation? The traditional approach has been to collect fetal blood from decapitation of fetuses. The new method of collecting fetal blood is from the fetal heart, and makes it possible to obtain pure fetal blood at near-term in rodents for fetal studies. This study also demonstrated a significant difference of fetal blood oxygen levels between the traditional and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…Fetal growth restriction in human (Regnault et al, 2007), and in large and small animals (Bauer et al, 2007), can be caused by multiple mechanisms, including in utero hypoxia (Viswanathan et al, 2007). It has been shown that maternal nicotine administration decreases fetal blood PO 2 in animals including rats (Socol et al, 1982;Mao et al, 2007). Notably, fetal brain weight was also significantly decreased by nicotine treatment in the present study.…”
Section: Discussionsupporting
confidence: 67%
“…Fetal growth restriction in human (Regnault et al, 2007), and in large and small animals (Bauer et al, 2007), can be caused by multiple mechanisms, including in utero hypoxia (Viswanathan et al, 2007). It has been shown that maternal nicotine administration decreases fetal blood PO 2 in animals including rats (Socol et al, 1982;Mao et al, 2007). Notably, fetal brain weight was also significantly decreased by nicotine treatment in the present study.…”
Section: Discussionsupporting
confidence: 67%
“…This makes analysis of blood values complicated and difficult. In the present study, we developed a method to collect fetal blood samples directly from the fetal heart in fetal rats for measurement of blood pO 2 , pCO 2 , O 2 saturation, pH, and lactic acid (Mao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several important nuclei located around the ventricular area, including the paraventricular nuclei, subfornical organ, median preoptic nuclei, and supraoptic nuclei, play an important role in water and salt intake in response to i.c.v. Ang II (Fitzsimons, 1998; Davisson et al, 2000; Mao et al, 2007a, b). Those areas around the ventricular system are also rich of Ang II receptors (Fitzsimons, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal, fetal, and adult offspring blood samples were collected into ice-cold plastic tubes as reported (Mao et al, 2007a, b). Briefly, fetal blood samples (7–8 fetuses from the same dam as n =1, and n =6–8, each group) were collected directly from the heart using intracardiac puncture, and blood was pooled together in the same litter.…”
Section: Methodsmentioning
confidence: 99%